Introduction to k- Horadam hybrid numbers - Nayil Kilic (Kuwait Journal of Science)
In this paper, we consider the k-Horadam hybrid numbers and investigate some of their properties. We also give some applications related to the k-Horadam hybrid numbers in matrices.